2012
DOI: 10.1007/s00127-012-0543-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimated rates of mental disorders in, and situational characteristics of, incidents of nonfatal use of force by police

Abstract: Psychoses and schizophrenia are dramatically overrepresented in cases where police resort to using force. Situational characteristics evident in the encounters are suggestive of a sub-group of people with mental disorders presenting with aggressive and otherwise problematic behaviours coupled with histories of criminal offending; this presents significant ongoing challenges for the police.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…The evidence base in this area has traditionally focused on lethal use of force, especially officer-provoked suicide involving mentally ill people. Literature from Canada Cotton 2010, Parent 2011), the United States of America (Deane et al 1999), Australia (Godfredson et al 2010, Kesic et al 2013a, 2013b and the United Kingdom (Moore 2010) confirms the over-representation of mentally ill or/and intoxicated people involved in such encounters with the police. Hence, a natural conclusion, perhaps, made by a number of prominent authors is that the police are not sufficiently prepared or trained to successfully manage situations involving people who are experiencing mental illness who present in distress and/or behave violently (Brouwer 2005, Cotton and.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…The evidence base in this area has traditionally focused on lethal use of force, especially officer-provoked suicide involving mentally ill people. Literature from Canada Cotton 2010, Parent 2011), the United States of America (Deane et al 1999), Australia (Godfredson et al 2010, Kesic et al 2013a, 2013b and the United Kingdom (Moore 2010) confirms the over-representation of mentally ill or/and intoxicated people involved in such encounters with the police. Hence, a natural conclusion, perhaps, made by a number of prominent authors is that the police are not sufficiently prepared or trained to successfully manage situations involving people who are experiencing mental illness who present in distress and/or behave violently (Brouwer 2005, Cotton and.…”
Section: Introductionmentioning
confidence: 75%
“…Indeed, studies have suggested that the presence of substance use is common in mental health crisis incidents and even considered to be the trigger of the incident by police in over one in five cases (Short et al 2013). When all of these elements are present together, the police are more likely to report to having to resort to using force to resolve the situation (Garner and Maxwell 2002, Police Complaints Authority 2003, Kesic et al 2013a, 2013b. Despite an increasing understanding of some of the common 'ingredients' of these potentially volatile situations, what remains unclear at this time is a detailed understanding of the decision-making behind the officer's decision to use force and how individual perceptions of dangerousness inevitably impact on this process.…”
Section: Research On Police Use Of Forcementioning
confidence: 97%
See 1 more Smart Citation
“…However, people with a mental illness are more likely to have force used against them by police (Kesic et al . ) and are more likely to be fatally wounded by police use of force (Kesic et al . ) than general community members.…”
Section: Discussionmentioning
confidence: 99%
“…By then, the person might have lost insight into their illness and might resist police if confronted (Roberts 2014). However, people with a mental illness are more likely to have force used against them by police (Kesic et al 2012) and are more likely to be fatally wounded by police use of force (Kesic et al 2010) than general community members. The current MHA effectively legislates against early intervention and inadvertently favours police interventions (Bradbury et al 2014).…”
Section: Discussionmentioning
confidence: 99%